Conditional lethality profiling reveals anticancer mechanisms of action and drug-nutrient interactions - Flickinger, Kyle M.; Wilson, Kelli M.; Rossiter, Nicholas J.; Hunger, Andrea L.; Vishwasrao, Paresh V.; Lee, Tobie D.; Mellado Fritz, Carlos A.; Richards, Rebecca M.; Hall, Matthew D.; Cantor, Jason R. (Science advances, 2024)
Chemical screens across hundreds of cell lines have shown that the drug sensitivities of human cancers can vary by genotype or lineage. However, most drug discovery studies have relied on culture media that poorly reflect metabolite levels in human blood. Here, we perform drug screens in traditional and Human Plasma–Like Medium (HPLM). Sets of compounds that show conditional anticancer activity span different phases of global development and include non-oncology drugs. Comparisons of the synthetic and serum-derived components that comprise typical media trace sets of conditional phenotypes to nucleotide synthesis substrates. We also characterize a unique dual mechanism for brivudine, a compound approved for antiviral use. Brivudine selectively impairs cell growth in low folate conditions by targeting two enzymes involved in one-carbon metabolism. Cataloged gene essentiality data further suggest that conditional phenotypes for other compounds are linked to off-target effects. Our findings establish general strategies for identifying drug-nutrient interactions and mechanisms of action by exploiting conditional lethality in cancer cells. Chemical screens identify drug sensitivities that vary in conventional versus Human Plasma–Like Medium (HPLM).